A Study On Surface Roughness During Fused Deposition Modelling: A Review - Harun, Nurul Hatiqah; Kasim, Mohd Shahir; Zainal Abidin, Muhammad Zaimi; Raja Abdullah, Raja Izamshah; Attan, Hassan; Ganesan, Hema Nanthini (Penerbit Universiti, UTeM, 2018)
Rapid Prototyping (RP) is technology used to produce a physical model or prototype directly from three-dimensional Computer-Aided-Design (3D CAD) data in a very short time. Fused Deposition Modelling (FDM) is a process for developing RP objects from plastic material by laying tracks of semi molten plastic filament on to a platform in precise layers from bottom to top. RP has been extensively used by manufacturers from different backgrounds to accelerate their product development and cycle time without neglecting product quality. In the RP process, surface finish is an important criterion as it can influence the part precision, post-handling expenses and functionality of the part. This paper presents a review of current studies on surface roughness using FDM. This paper also highlights design of experiments (DOE) and its association with surface finish.